The Collapse of a Legacy: Analyzing Bata’s Financial Struggles (2019-2023) - Salsabilla, Putri; Cheisviyanny, Charoline (Jurnal Eksplorasi Akuntansi, 2025)
This research is encouraged by the closure of the Bata Shoe factory in Purwakarta in early 2024. The aim of the research is to analyze financial factors that can provide going concern signals for PT Sepatu Bata Tbk for the 2019-2023 period. The type of research conducted is quantitative descriptive research. This study uses secondary data in the form of annual reports of PT Sepatu Bata Tbk for the 2019-2023 period obtained from the Indonesia Stock Exchange. Data analysis in this study uses two stages, namely data interpretation and conclusion drawing. The results of this study indicate that analysis using the Altman Z Score method, financial distress indicators and financial ratios can give going concern signals for PT Sepatu Bata Tbk for the 2019-2023 period.